Investing in Socially Responsible Companies is a must for Public Pension Funds – Because there is no Better Alternative - Sethi, S. Prakash (Journal of business ethics, 2005)
>With assets of over US$1.0 trillion and growing, public pension funds in the United States have become a major force in the private sector through their holding of equity positions in large publicly traded corporations. More recently, these funds have been expanding their investment strategy by considering a corporation’s long-term risks on issues such as environmental protection, sustainability, and good corporate citizenship, and how these factors impact a company’s long-term performance. Conventional wisdom argues that the fiduciary responsibility of the pension funds’ trustees must be solely focused on their beneficiaries and, therefore, their investment criteria must be based strictly on narrowly defined financial measures. It is also asserted that well-established financial measurements of corporate performance already include long-term risk assessment through discounted present value of future flow of earnings. Consequently, all other criteria are contrary to the best interest of the pension funds’ beneficiaries. In this paper, we assert that, contrary to conventional wisdom, pension funds, and for that matter other mutual funds, must be concerned with the long-term survival and growth of corporations. These measures are generally referred to “socially responsible investing’’ (SRI) and when applied to corporations, it is termed “socially responsible corporate conduct (SRCC).” We demonstrate that current measurement of future risk assessment invariably understates, and quite often completely overlooks, these long-term risks because of the inherent bias towards short-run on the part of financial intermediaries whose compensation depends greatly on short-term results. Furthermore, there is ample evidence to suggest that these intermediaries have been engaging in self-serving practices and thus failing in their duties to serve their clients’, i.e. pension funds’, best interests. Because of their large holdings in the total market as well as individual companies, these funds cannot easily divest from poorly performing companies without destabilizing the companies’ stock and overall markets. Hence, they must opt for a strategy of emphasizing investment criteria that encourage companies to take into account long-term aspects of their operations in terms of their impact on environment, sustainability, and community welfare, to name a few. We argue that an exclusionary, and even a primary, focus on short-term financial criteria is no longer a viable option. It also calls for the pension funds to encourage greater transparency and accountability of the entire corporate sector through improved corporate governance. Thus socially responsible investing practices are not merely discretionary and desirable activities; they are a necessary imperative, which both the corporations and public pension funds, and other large institutional holders, will ignore at serious peril to themselves. Finally, the paper considers some of the recent developments where corporations have been responding to these challenges and how their actions might be strengthened through greater disclosure and transparency of corporate activities. It also makes recommendations for the pension funds to support further research in creating new measurement standards that further refine the concept of socially responsible investing as a necessary ingredient of long-term corporate survival and growth in the context of a changing economic, environmental and socio-political dynamic.